The Enduring Legacy: Oil, Culture, and Society in Venezuela (AmeriQuests, 2011)
This review discusses the conceptual interventions that Salas makes in the fields of Venezuelan history, studies of extraction economics, and international relations between Latin America, the U.S., and Europe. Salas argues that the rise of the oil industry in Venezuela impacted not only Venezuela's economy and foreign relations but also its cultural and social formations. I summarize Salas's main points and examine the strengths of his book: his archival research, his synthesis of detail into a cohesive picture, and his interesting conceptual turn away from the idea of oil as an agent of modernization. I also recognize the absence of indigenous voices from Salas's account and attribute this to gaps that exist in the archival material.
Keywords: oil; culture; race; national identity